Strain engineering of vertical molybdenum ditelluride phase-change memristors - Hou, Wenhui; Azizimanesh, Ahmad; Dey, Aditya; Yang, Yufeng; Wang, Wuxiucheng; Shao, Chen; Wu, Hui; Askari, Hesam; Singh, Sobhit; Wu, Stephen M (Nature electronics, 2024)
Electric-field-controlled electronic and structural phase transitions can be used as a mechanism for memristive switching in two-dimensional (2D) materials. However, such 2D phase-change memristors do not typically outperform other 2D memristors. Here we report high-performance bipolar phase-change memristors that are based on strain-engineered multilayer molybdenum ditelluride (MoTe2). Using process-induced strain engineering, stressed metal thin films are patterned into contacts that induce a strain-driven semimetallic-to-semiconducting phase transition in the MoTe2, forming a self-aligned vertical transport memristor with semiconducting MoTe2 as the active region. By using strain to bring the material close to the phase transition boundary, the devices can exhibit switching voltages of 90 mV, on/off ratios of 108, switching times of 5 ns and retentions of over 105 s. A single-process parameter, contact metal film force (the product of the film stress and film thickness), can be varied to tune the device switching voltage and on/off ratio.Memristors based on electric-field-induced phase transitions between a semiconducting and conductive phase of molybdenum ditelluride can be improved by using stressed metal contacts to strain the material closer to the phase switching point.